Are L1 and L2 strategies transferable? An exploration of the L1 and L2 writing strategies of Chinese graduate students. Issue 6 (1st November 2020) - Guo, Xiaoqian; Huang, Li-Shih
ABSTRACT: Over the past three decades, second language writing has witnessed a growth of studies on learners' writing strategies, as well as a shift from product-oriented to process-oriented research. Although the field has achieved a greater understanding of strategies used by English-as-an-additional-language (EAL) writers, limited research has examined the strategies used by learners in completing the same writing task in their L1 (first language) versus L2 (second language). Such an exploration would shed light on the transferability of writing strategies between L1 and L2 in different writing tasks. The present study used a questionnaire, concurrent think-aloud protocol and immediate post-task retrospective interviews to examine the strategies used by 35 Chinese EAL learners in completing L1 and L2 writing tasks and how these strategies related to writing performance. Results pertaining to the identified L1 and L2 writing strategies, similarities and differences between L1 and L2 writing strategy use, the potential transferability of L1 and L2 strategy use in writing, and strategy use in relation to writing performance are reported and discussed in relation to previous research. Also considered are implications, limitations and future research directions to move the field forward.